2017
DOI: 10.1139/facets-2017-0077
|View full text |Cite
|
Sign up to set email alerts
|

“It was kind of like if it happens it happens. It wasn’t planned, it wasn’t intentional”: Young mothers’ experiences with subsequent pregnancy in Ottawa, Canada

Abstract: Young mothers constitute a vulnerable population in Canada. Teens with children are at significant risk of subsequent pregnancy, a dynamic that can exacerbate health, emotional, and socio-economic challenges. We aimed to understand better the dynamics shaping "rapid repeat pregnancy" among young mothers in Ottawa, explore young mothers' subsequent pregnancy experiences, and identify how services could be improved in Canada's capital. In 2016, we conducted in-depth interviews with 10 young mothers and semi-stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
1
2
0
1
Order By: Relevance
“…As noted above, one quarter of the women (25 percent) in the sample disagreed or disagreed strongly that it is important to plan pregnancies. This finding challenges the assumption sometimes made by fertility researchers that virtually all women endorse the planning schema and supports the claim made by many that women differ in the importance they attribute to the idea of planning pregnancies (Barrett and Wellings 2002;Borrero et al 2015;Fortier and Foster 2017;Geist et al 2019;Gomez et al 2018;Hernandez et al 2020;Jones 2018;Kendall et al 2005;Rocca et al 2013;Shreffler et al 2012). The results also demonstrate that, contrary to assumptions in much research on "unintended pregnancies," a substantial minority of women are not planful, but rather nearly a third described themselves as okay either way at the time of their pregnancies.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…As noted above, one quarter of the women (25 percent) in the sample disagreed or disagreed strongly that it is important to plan pregnancies. This finding challenges the assumption sometimes made by fertility researchers that virtually all women endorse the planning schema and supports the claim made by many that women differ in the importance they attribute to the idea of planning pregnancies (Barrett and Wellings 2002;Borrero et al 2015;Fortier and Foster 2017;Geist et al 2019;Gomez et al 2018;Hernandez et al 2020;Jones 2018;Kendall et al 2005;Rocca et al 2013;Shreffler et al 2012). The results also demonstrate that, contrary to assumptions in much research on "unintended pregnancies," a substantial minority of women are not planful, but rather nearly a third described themselves as okay either way at the time of their pregnancies.…”
Section: Discussionsupporting
confidence: 65%
“…There is some evidence, however, suggesting that not all women embrace the planning schema but rather that women differ in the salience they attribute to the idea of planning pregnancies (Barrett and Wellings 2002; Borrero et al 2015; Fortier and Foster 2017; Geist et al 2019; Jones 2018; Kendall et al 2005; Rocca, Harper, and Raine-Bennett 2013). Shreffler et al (2012) found, in a qualitative study of 56 lower income women of reproductive age in a south central city, that 27 percent of their sample felt that planning one’s pregnancies is only moderately important and that 21 percent held it to be of little or no importance.…”
Section: Introductionmentioning
confidence: 99%
“…Nonuse of contraception could be a sign that a woman is open to the idea of getting pregnant even if she does not report that she is purposely trying to do so. Some situations where women are not actively trying to get pregnant but not using contraception might be considered a type of “passive” pregnancy planning [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Isso se justifica porque muitas mulheres participantes deste estudo ainda pretendem ter filhos ou estão indecisas quanto a isso e são justamente essas mulheres as que têm maior probabilidade de descontinuar o uso de MAC (Moreau et al, 2010;Modey, Aryeetey, Adanu, 2014). Esse achado corrobora com outros estudos que indicam que nem todas mulheres com experiência de certos eventos reprodutivos, como gravidez e abortamento, modificam seus comportamentos de forma a influenciar a prevenção de gravidez não planejada (Moreau et al, 2010;Modey, Aryeetey, Adanu, 2014;Fortier, Foster, 2017 (Ali, Cleland, 2005;Moreau, Cleland, Trussell, 2007;Leite, Gupta, 2007;Murphy, Brixner, 2008;Vaughan et al, 2008). Em outro estudo brasileiro, realizado com 12.612 mulheres de 15 a 49 anos, sua taxa de descontinuidade foi 63,7% em 12 meses de uso, bem maior do que a observada neste estudo (Leite, Gupta, 2007).…”
Section: Descontinuidades No Uso Da Pílula Oral E Fatores Associadosunclassified